Peran Smart People dalam Meningkatkan Perekonomian Keluarga di Kelurahan Kertapati Palembang - Yunita Febriani; Randi Hidayat; Sudarta, Sudarta; Primasari Fitria; Amrah Muslimin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Globalization changes have changed human civilization both in terms of behavioral patterns and the economy. People are able to become smart people as supporters of the family economy. Kertapati Village is an area in Palembang City, this village is famous for its expertise in utilizing natural products in the form of fish to be managed to become consumption products that can be sold in the form of pempek and crackers, besides that the community also has craft skills in processing cloth into raw materials for making their typical clothes, namely jumputan. The abundance of raw materials owned and the skills possessed are actually still unable to provide support for the family economy. So the purpose of this community service activity is focused on providing an overview to the community that it is important to manage change and utilize smart people in supporting the family economy. The method used in this activity is the Research on Participation (PAR) method by involving the participation of the Kertapati village community. The results of this activity show that the community is able to follow, observe, understand, discuss and plan in creating opportunities and developing the abilities and efforts they have in supporting the family economy.